UTILIZING PROBLEM-BASED LEARNING MODEL TO IMPROVE STUDENTS’ MATHEMATICAL REPRESENTATION ABILITY - Rahmi Islamiat; Yurniwati; AR Supriatna (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was a qualitative descriptive study using library research methods and aimed to study the application of problem-based learning model to improve students' mathematical representation ability. The data came from scientific articles, books, and thesis limited from 2014-2020 at least at the SINTA 4 level on a national and international scale with relevant variables. Based on the results of studies and data analysis, it was concluded that the application of problem-based learning models affected students' mathematical representation ability at every level of education. Problem-based learning contributed to improve students' mathematical representation ability and other aspects such as learning motivation, selfefficacy, and mathematical disposition.